1996
DOI: 10.1093/ndt/11.supp8.42
|View full text |Cite
|
Sign up to set email alerts
|

Sodium profiling in elderly haemodialysis patients

Abstract: Intradialytic vascular instability continues to be one of the most frequent complications in elderly haemodialysis patients. Signs of impending hypotension such as sweating, apprehension, tachycardia, nausea, or vomiting may be infrequent in the geriatric population. The onset of hypotension in the elderly may be sudden and profound and may lead to serious consequences such as myocardial infarction, stroke, or aspiration if not treated promptly. Prevention of vascular instability is extremely important in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
1
12
2
Order By: Relevance
“…With regard to the possibility of profiling causing sodium accumulation, it is worth noting that there was no follow‐up of predialysis and/or postdialysis sodium levels or of clinical signs of sodium accumulation in six of the studies (12, 20–22, 24,33). Clinical or laboratory signs of sodium accumulation were found in eight studies (9,13,19,23,25,27,29,31) but not in the other eight cases (4,14,18,26,28,30,32,34). In one of these investigations (4), a decreasing sodium profile reduced serum sodium levels to normal or even hyponatremic values and led to a decrease in thirst and interdialytic weight gain.…”
Section: Sodium Profilingmentioning
confidence: 85%
See 3 more Smart Citations
“…With regard to the possibility of profiling causing sodium accumulation, it is worth noting that there was no follow‐up of predialysis and/or postdialysis sodium levels or of clinical signs of sodium accumulation in six of the studies (12, 20–22, 24,33). Clinical or laboratory signs of sodium accumulation were found in eight studies (9,13,19,23,25,27,29,31) but not in the other eight cases (4,14,18,26,28,30,32,34). In one of these investigations (4), a decreasing sodium profile reduced serum sodium levels to normal or even hyponatremic values and led to a decrease in thirst and interdialytic weight gain.…”
Section: Sodium Profilingmentioning
confidence: 85%
“…In addition to this, dialysis fluid sodium concentrations can be selected not only to prevent intracellular water uptake but also to support water transport into the extracellular space, that is, to support plasma refilling (9–14). However, the effect of sodium profiling on preserving EC volume is small compared to the volume depletion caused by ultrafiltration (11,15).…”
Section: Sodium Profilingmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of authors believe that the sodium profiling haemodialysis causes ‘interdialytic’ discomforts more frequently than the conventional haemodialysis in spite of its success in preventing intradialytic hypotensive episodes. In the review of previous studies, clinical or laboratory signs of sodium accumulation were found in eight studies, 2,3,7 , 8,34 , 39,40 ,41 but not in the other eight cases 4,37 , 42–47 . In one exceptional study in which the sodium was profiled from 137 to 128 mmol/L, the decreases of serum sodium levels, thirst, and interdialytic weight gain were observed 43 .…”
Section: Clinical Results Of Sodium Profiling Haemodialysismentioning
confidence: 96%